When the Client Is a Former Auditor: Auditees' Expert Knowledge and Social Capital as Threats to Staff Auditors' Operational Independence - Daoust, Laurence; Malsch, Bertrand (Contemporary Accounting Research, 2020)
ABSTRACT Auditees can play an active role in influencing staff auditors' professional judgment and skepticism. Yet, although it constitutes one of the main threats to auditor independence, very little is known about the means and extent of auditees' power during the audit engagement. To address this knowledge gap, our study focuses on a specific category of auditees, namely, auditees who have worked as auditors in large accounting firms. We interviewed 36 of these auditees and triangulated our findings with 11 interviews conducted with auditors. At the theoretical level, we conceptualize auditees' influence over auditors as intentional and active through the notion of “social power.” Overall, our analysis shows that the efficacy of auditees' power during the engagement materializes through the mobilization of two main power resources developed during their time at the firms: (i) expert knowledge of auditing techniques and (ii) social capital. On the one hand, relying on their cognitive authority, auditees' employ three different power strategies to constrain staff auditors' operational independence: stage‐setting , teaching , and questioning . On the other hand, auditees' social capital can support the use of two additional strategies: attracting and monitoring . Our triangulation analysis confirms our findings and suggests that auditors may be aware of the threats to independence that auditee expertise and social capital pose. By focusing on auditees' agentic capabilities—that is, individuals' capabilities to consciously exert influence over the course of events—we reinterpret the pressures exerted by clients on auditors as the product of strategic actions and discuss substantive consequences for independence risk.